Oil and Gas Conference. Day 1. Tape 05. - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1979)
Questions posed to Ian Clarke (jurisdiction, population growth, national oil policy, community influence, safeguards during oil development, impact of oil on Shetlands, effect of oil on traditional industries, errors made during development).